The endophytic potential, Bacillus spp. for controlling Meloidogyne sp. and increasing tomato growth and production - Yanti, Yulmira; Hamid, Hasmiandy; Winarto, Winarto; Yaherwandi, Yaherwandi (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Meloidogyne spp. is responsible of root swelling, one of the primary disease in tomato plants. Controlling this nematode is challenging due to its wide host range. The use of synthetic nematicides harms the environment; therefore, alternative controls, such as biological methods, are necessary. Among the biological agents, one group includes endophytic bacteria that reside in plant tissues and do not cause harm to plants. These bacteria enhance plant resistance to pests and pathogens while promoting plant growth. The study aimed to acquire endophytes, Bacillus spp. strains capable of controlling Meloidogyne sp. while stimulating the growth of tomato plants. The research employed a completely randomized design (CRD) comprising seven treatments and five replications. The treatments consisted of B. cereus strain SNE 2.2, TLE 2.3 and TLE 1.1, B. pseudomycoides strain EPL 1.1.3, B. toyonensis strain EPL 1.1.4, positive control (without the introduction of Bacillus spp. and inoculation with Meloidogyne sp.) and negative control (without Bacillus spp. and without Meloidogyne sp.). Bacillus spp. endophyites were introduced in two stages: into the seeds and into the roots of tomato seedlings for 15 min. The observed variables were the development of Meloidogyne sp., endophytic colonization of Bacillus spp., and plant growth. The results demonstrated that all Bacillus spp. were effective in controlling Meloidogyne sp. and enhancing the growth of tomato plants. The best isolate in controlling Meloidogyne sp. and increasing the growth of tomato plants was B. cereus strain SNE2.2.